Management Control, Intrinsic Motivation and Creativity: How Can They Coexist? - Mikkel Godt Gregersen (Copenhagen Business School (CBS), 2017)
This thesis consists of a cape and three papers. The overall research question is: How can intrinsic motivation and management control coexist in a creative environment and how can coordination be possible in such a context? The cape ties together the research done in the three papers. It is divided into six sections. The first section introduces the concepts of intrinsic motivation, creativity and management control. This is followed by a section on management control in a creative context. These two sections frame the thesis and introduce the setting in which the research has been done. The third section presents the research approach, which is the application of basic needs as social mechanisms. Social mechanisms are used to explain one event by a previous event by identifying the causal links between the two events. Basic needs are the needs for feelings of autonomy, competence and relatedness. In section four, social mechanisms are positioned as a middle-ranged paradigm between the Interpretive and the Functionalist paradigms. Section five discusses the findings of the three papers and finally section six provides the answers to the research question as a conclusion. The first part of the conclusion is that intrinsic motivation and management control can coexist under the conditions that all three basic needs, i.e. autonomy, competence and relatedness, are supported. This can happen when control takes point of departure in the individual employee. The second part of the conclusion is that coordination (via management control) is possible in a creative context if control interacts directly with the creative process.
hdl:10398/9493
Keywords: 650